Gender Capability in Facing the Reality of the Impact of Forest Fires in Central Kalimantan - Sari Marlina, Bambang Supriyono Lautt, Aswin Usup, Revi Sunaryati (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Gender is an agent of change and also great dual agent for families, public and their communities. Women play an important role in natural resources management and participate in household life. The greatness of the gender as double agent is shown when a disaster occurs which affects economic and social condition. Natural disasters that often occur in Central Kalimantan due to the impact of climate change. This study aims to determine the extent to which gender is capable of solving problem with the impacts of climate change and what solutions and supports can improve gender equality. The research was conducted in 3 sub-districts in the Central Kalimantan region, namely Palangkaraya, Pulang Pisau and Kapuas. The method used was descriptive method by conducting interviews to determine gender capacity and adaptation to the impact of forest fires. The ability of gender in Central Kalimantan to deal with climate change shows that gender is a great agent when facing the declining economic conditions caused by forest fires and can still take care of the household. So that this condition requires support and concern for gender equality which can change difficult things when the impacts of climate change are present and can be used as a reference for reducing the impacts of climate change.